Culturing Learning vs Educating culture; A Study of Islamic Education in University - Lathifah Hanum (Proceeding International Seminar of Islamic Studies, 2019)
Islamic education touched a various aspect in education and human life. In university, Islamic education is a macro scope in every aspect. It also discuss about learning culture. This learning culture should be practice with a good and relevant characteristic and attitude until they build a habit called learning culture. Educating culture disposed by how the learning culture acquainted to university students. It means that it should improve learning culture quality through learning activity, reading a lesson, listening a lesson, writing a lesson, following a lesson , creating a research, and do a volunteering for public society. Learning culture in university has not a significant different with learning culture at school. Culturing learning and educating culture in university has a principle substance in andragogic learning.